The Kaputin: Anti-colonialism and Anti-masonry in the Philippines - Cuartero Escobes, Susana (2023)
The Spanish Pacific had become an uncontrollable keg of gun powder in the last third of the 19th century. Several unsolved troubles, aggravated over the time, came together on the same path and the battered foundations of an exhausted metropolis collapsed through an insurrection. The Bourbon monarchy’s policies in its overseas possessions forged an anti-colonial and anti-Masonic nationalist movement. This movement reached its peak in 1896, with the Tagalog insurrection and the definitive break away from Spain in 1898.